Bestial Traces : Race, Sexuality, Animality - Peterson, Christopher (Book collections on Project MUSE., 2012)
In contemporary race and sexuality studies, the topic of animality emerges almost exclusively in order to index the dehumanization that makes discrimination possible. Bestial Traces argues that a more fundamental disavowal of human animality conditions the bestialization of racial and sexual minorities. Hence, when conservative politicians equate homosexuality with bestiality, they betray an anxious effort to deny the animality inherent in all sexuality. Focusing on literary texts by Edgar Allan Poe, Joel Chandler Harris, Richard Wright, Philip Roth, and J.M. Coetzee, together with philosophical texts by Derrida, Heidegger, Agamben, Freud, and Nietzsche, Peterson maintains that the representation of social and political others as animals can be mitigated but never finally abolished. All forms of belonging inevitably exclude some others as Gbeasts. G Though one might argue that absolute political equality and inclusion remain desirable, even if ultimately unattainable, ideals, Bestial Traces shows that, by maintaining such principles, we exacerbate rather than ameliorate violence because we fail to confront how discrimination and exclusion condition all social relations.